2005
DOI: 10.1016/j.anbehav.2005.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Mate guarding and paternity in mandrills: factors influencing alpha male monopoly

Abstract: . (2005) This is the author's version of a work that was accepted for publication in Animal Behaviour. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be re ected in this document. Changes may have been made to this work since it was submitted for publication. Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(83 citation statements)
references
References 68 publications
4
78
1
Order By: Relevance
“…Even if a larger sample size would be required to test it definitively, our results support the notion that the a male was able to discriminate in favor of conceptive cycles [Alberts et al, 2006;Bulger, 1993;Deschner et al, 2004;Engelhardt et al, 2004;Gesquiere et al, 2007;Setchell et al, 2005b;Weingrill et al, 2003]. However, Bercovitch [1987] showed that male baboons did not act in a manner indicating that they could pinpoint a conception cycle in advance.…”
Section: Male-male Competition and Reproductive Skewsupporting
confidence: 56%
“…Even if a larger sample size would be required to test it definitively, our results support the notion that the a male was able to discriminate in favor of conceptive cycles [Alberts et al, 2006;Bulger, 1993;Deschner et al, 2004;Engelhardt et al, 2004;Gesquiere et al, 2007;Setchell et al, 2005b;Weingrill et al, 2003]. However, Bercovitch [1987] showed that male baboons did not act in a manner indicating that they could pinpoint a conception cycle in advance.…”
Section: Male-male Competition and Reproductive Skewsupporting
confidence: 56%
“…Males begin to develop secondary sexual adornments at 6-7 years of age [24,28] but do not attain social maturity or mate until they reach adulthood at more than 9 years old [23]. Using their especially long canines as weapons [29], adult males compete fiercely with each other, and only a few dominant individuals gain access to fertile females [30].…”
Section: Methodsmentioning
confidence: 99%
“…In particular, we know that high-ranking males are unable to monopolize reproductive opportunities when more than one female is simultaneously in oestrus; the effects of oestrus synchrony on male reproductive success are incorporated into the priority of access model, in which the degree of cycle overlap determines how many males will gain access to mates (Altmann 1962). In several recent studies, the priority of access model has been shown to be a good predictor of the mating patterns of cercopithecine primates living in multimale groups during at least some periods of time (Bulger 1993;Weingrill et al 2000;Alberts et al 2003;Weingrill et al 2003;Takahashi 2004;Setchell et al 2005). Furthermore, when the priority of access model does not predict mating patterns, the model has provided a useful framework for understanding the dynamics of maleemale competition (e.g.…”
mentioning
confidence: 99%